Elevated levels of invariant natural killer T-cell and natural killer cell activation correlate with disease progression in HIV-1 and HIV-2 infections. (17th July 2016) - Bächle, Susanna M.; Malone, David F.G.; Buggert, Marcus; Karlsson, Annika C.; Isberg, Per-Erik; Biague, Antonio J.; Norrgren, Hans; Medstrand, Patrik; ,; Moll, Markus; Sandberg, Johan K.; Jansson, Marianne
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: In this study, we aimed to investigate the frequency and activation of invariant natural killer T (iNKT) cells and natural killer (NK) cells among HIV-1, HIV-2, or dually HIV-1/HIV-2 (HIV-D)-infected individuals, in relation to markers of disease progression. Design: Whole blood samples were collected from treatment-naive HIV-1 ( n  = 23), HIV-2 ( n  = 34), and HIV-D ( n  = 11) infected individuals, as well as HIV-seronegative controls ( n  = 25), belonging to an occupational cohort in Guinea-Bissau. Methods: Frequencies and activation levels of iNKT and NK cell subsets were analysed using multicolour flow cytometry, and results were related to HIV-status, CD4 + T-cell levels, viral load, and T-cell activation. Results: HIV-1, HIV-D, and viremic HIV-2 individuals had lower numbers of CD4 + iNKT cells in circulation compared with seronegative controls. Numbers of CD56 bright NK cells were also reduced in HIV-infected individuals as compared with control study participants. Notably, iNKT cell and NK cell activation levels, assessed by CD38 expression, were increased in HIV-1 and HIV-2 single, as well as dual, infections. HIV-2 viremia was associated with elevated activation levels in CD4 + iNKT cells, CD56 bright, and CD56 dim NK cells, as compared with aviremic HIV-2 infection. Additionally, disease markers such as CD4 + T-cell percentages, viral load, and CD4 + T-cell activation were associated with CD38 expression levels of both iNKT and NK cells, which activation levels also correlated with each other. Conclusion: Our data indicate that elevated levels of iNKT-cell and NK-cell activation are associated with viremia and disease progression markers in both HIV-1 and HIV-2 infections.